Accuracy of Neutrophil to Lymphocyte Ratio in Predicting for Rupture Appendicitis Patient in Uttaradit Hospital - Lormuangthong, Nichanart; Khumpasung, Phakkaphol; Musikpodok, Nawinda (Health Science Clinical Research, 2022)
Introduction : Ruptured appendicitis is the most serious complications of acute appendicitis. The incidence is 2.9 per 10,000 persons. Because of the delayed diagnosis, there are more postoperative complications. When inflammatory biomarkers were investigated to predict ruptured appendicitis, the neutrophil to lymphocyte ratio (NLR) was found to be the most responsive. However, there are limitations in the selection of population that have a significant effect on the NLR, such as age and underlying disease. As a result, a study of patients 15-60 years without underlying disease was conducted. Objective : To investigate the accuracy of NLR in predict ruptured appendicitis and to determine the cutoff value of NLR in predict ruptured appendicitis in Uttaradit hospital patients. Method : From November 3rd 2019 to November 3rd 2021, 328 appendectomy patients aged 15-60 years were studied at Uttaradit hospital. There were 273 patients with appendicitis without complications and 55 patients with ruptured appendicitis included. Data was collected from ICD-10 medical records (K35), which were separated into two groups. All data were analyzed by descriptive and analytic statistics. Conclusion: The NLR cutoff value of 7.1 can significantly predict appendicitis rupture. Other factors should be considered to improve accuracy. The NLR can be used as a guideline for making decisions about referring patients to appropriate medical centers, treatment, informing patients and families.